Postfix : the definitive guide - Dent, Kyle D. (O'Reilly, 2004)
Postfix is a Mail Transfer Agent (MTA): software that mail servers use to route email. Postfix is highly respected by experts for its secure design and tremendous reliability. And new users like it because it's so simple to configure. In fact, Postfix has been adopted as the default MTA on Mac OS X. It is also compatible with sendmail, so that existing scripts and programs continue to work seamlesslyafter it is installed. Postfix was written by well-known security expert Wietse Venema, who reviewed this book intensively during its entire development. Author Kyle Dent covers a wide range of Postfix tasks, from virtual hosting to controls for unsolicited commercial email. While basic configuration of Postfix is easy, every site has unique needs that call for a certain amount of study. This book, with careful background explanations and generous examples, eases readers from the basic configuration to the full power of Postfix. It discusses the Postfix interfaces to various tools that round out a fully scalable and highly secure email system. These tools include POP, IMAP, LDAP, MySQL, Simple Authentication and Security Layer (SASL), and Transport Layer Security (TLS, an upgrade of SSL). A reference section for Postfix configuration parameters and an installation guide are included. Topics include: Basic installation and configuration DNS configuration for email Working with POP/IMAP servers Hosting multiple domains (virtual hosting) Mailing lists Handling unsolicited email (spam blocking) Security through SASL and TLS From compiling and installing Postfix to troubleshooting, Postfix: The Definitive Guide offers system administrators and anyone who deals with Postfix an all-in-one, comprehensive tutorial and reference to this MTA.